Awareness of Farmers Related Crop Production Technology in Sagar, Madhya Pradesh (Indian Journal of Extension Education, 2011)
A large number of illiterate farmer in the country are in the habit of sticking with old farm practice. They are poorly educated having low credit flow from institutions which adversely effect the adoption of farm practices. Through up gradation in skill the farmer can able to under stand the new practice of agriculture technology and get benefit. Knowledge has been found to be an important factor contributing to the adaptation of innovation by farmers. The present investigation conducted in Sager district of M.P. The data were collected on 14 agronomical practice of 4 major crop Soybean, Arhar, Wheat and chick pea that whether they have aware or not. It has been again evidence from the study that awareness of the farmer about improve farm practice was very low in case of fertilizer requirement, improved verities, plant protection practices, optimum time of sowing and weed management as reported by majority of respondent data also revealed that their was correlation between awareness and education, caste, land holding, income, material possession, social participation and attitude. It is interesting to note that there still a big gap between the available crop production technology and technologies received and adopted by the farmer. Which altimetry affect the livelihood of the farmers.